Increased expression of matrix metalloproteinase 3 can be attenuated by inhibition of microRNA-155 in cultured human astrocytes - Anatoly Korotkov; Diede W. M. Broekaart; Jackelien van Scheppingen; Jasper J. Anink; Johannes C. Baayen; Sander Idema; Jan A. Gorter; Eleonora Aronica; Erwin A. van Vliet (Journal of Neuroinflammation, 2018)
Abstract Background Temporal lobe epilepsy (TLE) is a chronic neurological disease, in which about 30% of patients cannot be treated adequately with anti-epileptic drugs. Brain inflammation and remodeling of the extracellular matrix (ECM) seem to play a major role in TLE. Matrix metalloproteinases (MMPs) are proteolytic enzymes largely responsible for the remodeling of the ECM. The inhibition of MMPs has been suggested as a novel therapy for epilepsy; however, available MMP inhibitors lack specificity and cause serious side effects. We studied whether MMPs could be modulated via microRNAs (miRNAs). Several miRNAs mediate inflammatory responses in the brain, which are known to control MMP expression. The aim of this study was to investigate whether an increased expression of MMPs after interleukin-1β (IL-1β) stimulation can be attenuated by inhibition of the inflammation-associated miR-155. Methods We investigated the expression of MMP2, MMP3, MMP9, and MMP14 in cultured human fetal astrocytes after stimulation with the pro-inflammatory cytokine IL-1β. The cells were transfected with miR-155 antagomiR, and the effect on MMP3 expression was investigated using real-time quantitative PCR and Western blotting. Furthermore, we characterized MMP3 and miR-155 expression in brain tissue of TLE patients with hippocampal sclerosis (TLE-HS) and during epileptogenesis in a rat TLE model. Results Inhibition of miR-155 by the antagomiR attenuated MMP3 overexpression after IL-1β stimulation in astrocytes. Increased expression of MMP3 and miR-155 was also evident in the hippocampus of TLE-HS patients and throughout epileptogenesis in the rat TLE model. Conclusions Our experiments showed that MMP3 is dynamically regulated by seizures as shown by increased expression in TLE tissue and during different phases of epileptogenesis in the rat TLE model. MMP3 can be induced by the pro-inflammatory cytokine IL-1β and is regulated by miR-155, suggesting a possible strategy to prevent epilepsy via reduction of inflammation.